IbMKELOMPOKUSAHA KECIL KRUPUK DI KENJERAN KOTA SURABAYA - Siti Mujanah; Tri Ratnawati; Wiwik Retnaningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
The purpose of the activities for the community IbM is to provide appropriatetechnology for Small Businesses engaged in Krupuk Shells. The objective of this activityis IbM three (3) business owners in the field of crackers in the area Kenjeran. Problemsfaced by Sme Krupuk is the low capability in the production of chips so that theirproducts are less if the fries are less able to expand and it does not feel as most vitsin,besides chips business is done by hand in mixing the chips is by churning by hand, aswell as in cooking with pot coming from the drums were very doubtful of hygiene andhealth, in addition to the practice of business management has not been in touch in theconduct of business, for example, to market the production to just wait for customers tocome, and there are no financial records so that they confuse the money business withthe household money. Proposer activities IbM have agreed with all three partners toprocure the technology in the production of which is to buy machinery Mixer materialcrackers, pot to cook the dough crackers, accompanied by the also given training in theproduction of crackers are tasty and higienes, as well as training in businessmanagement, finance and marketing strategy.Keyword : Crackers production, appropriate technology, and BusinessManagement